The Effect of Anesthesia Nursing Care Writing Training on Increasing Readiness to Guide Preceptors - Anggeriyane, Esme; Suwandewi, Alit; Aprilia, Hanura; Mariani, Mariani; Mathuridy, Roly Marwan; Norfriati, Norfriati (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Good nursing care plays an important role in helping patients achieve optimal health. Clinical preceptors play a significant role in the learning process of prospective nurse anesthesia students. Qualified preceptors are equipped with knowledge and skills through special training. This study aims to evaluate the effectiveness of preceptorship training on the competency of anesthesia clinic preceptors. This type of quasi-experimental research with a pretest-posttest design. The research subjects were preceptors in the OK, IGD, RR and ICU rooms at Banjarmasin and Banjarbaru city hospitals. This research uses an instrument in the form of a readiness questionnaire to guide preceptors. The results showed that before training, 15 preceptors (44.1%) had sufficient readiness to guide the writing of nursing care. After training, 33 preceptors (97.1%) showed good readiness. The Wilcoxon test produces a value of p = 0.000 (p 0.05), which shows a significant effect of preceptorship training on preceptor readiness in guiding. Preceptorship training is effective in increasing the competency of clinical preceptors in guiding nursing care, so this training is important to carry out on an ongoing basis to improve the quality of nursing education and practice.